Association Between the Two-Year Trajectories of Dental Anxiety and the Changes in the Oral Health-Related Quality of Life in Parents of FinnBrain Birth Cohort Study - Yang Lily; Suominen Auli; Palo Katri; Kataja Eeva-Leena; Pohjola Vesa; Ogawa Mika; Karlsson Linnea; Karlsson Hasse; Laakkonen Eero; Lahti Satu (MDPI AG, 2025)
Objectives: We evaluated associations between changes in dental anxiety and oral health-related quality of life (OHRQoL) in parents of the FinnBrain Birth Cohort Study.
Methods: Two-year dental anxiety trajectories measured with Modified Dental Anxiety Scale from gestational weeks (gw) 14 and 34, and 3 and 24 months after birth were used. OHRQoL was measured with the Oral Health Impact Profile 14-item questionnaire at gw34 and 4 years. Changes in the OHRQoL sum and dimension scores according to dental anxiety trajectories were analyzed with the Jonckheere–Terpstra test separately for mothers (n = 998) and fathers (n = 513).
Results: Overall, OHRQoL decreased in all dental anxiety trajectory groups except the High decreasing group in mothers, and in the Stable high group in fathers. The decline in the overall OHRQoL was greatest in the Stable high trajectory group for both parents. In fathers, OHRQoL increased considerably but not statistically significantly in the High decreasing trajectory group. The changes in OHRQoL dimensions Psychological discomfort and Handicap differed according to dental anxiety trajectories for both of mothers and fathers, and also for the dimension Psychological disability for mothers.
Conclusions: These findings highlight the need for targeted interventions in treating high dental anxiety and in preventing the increase in dental anxiety to improve oral health outcomes such as OHRQoL.